“Story of a Bank” Basel II accreditation through university-industry collaboration-case study - Liew, Choon Kiat; Dileep Kumar M., (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper deals with a case study of credit risk scoring models at Industrial Bank. The aim of this research is to investigate how a Malaysian financial institution developed and integrated credit risk scoring models with current organisational needs and evaluation of best practices for university-industry collaboration on this initiative. Attempts were made to categorise the credit risk scoring models initiative according to a variety of statistical techniques from modeling. This is an exploratory study which uses qualitative research methodology. Analysis of document from company annual reports as well as articles from journal, Bank Negara Malaysia, (BNM) regulatory reports as well as working papers and semistructured interviews were conducted to identify the organisational needs as a result of context and task. A company-wide development system for credit risk scoring model was effectively integrated to provide a direct support to competence management endeavor. The company’s credit risk scoring models initiatives have also resulted in managerial implications such as increased effectiveness of risk management through measuring the riskiness of each customer and automated the whole process, thereby leading to significant efficiency improvements. Thus, scoring models help banks to control credit risks. Going forward, credit risk scoring model is to become the best practice approach of the receivables management process and is essential to effective credit risk management.